A Simple Evaluation Tool (ET-CET) Indicates Increase of Diagnostic Skills From Small Bowel Capsule Endoscopy Training Courses: A Prospective Observational European Multicenter Study. Issue 43 (October 2015) - Albert, J.G.; Humbla, O.; McAlindon, M.E.; Davison, C.; Seitz, U.; Fraser, C.; Hagenmüller, F.; Noetzel, E.; Spada, C.; Riccioni, M.E.; Barnert, J.; Filmann, N.; et al.
Abstract : Abstract: Small bowel capsule endoscopy (SBCE) has become a first line diagnostic tool. Several training courses with a similar format have been established in Europe; however, data on learning curve and training in SBCE remain sparse. Between 2008 and 2011, different basic SBCE training courses were organized internationally in UK (n = 2), Italy (n = 2), Germany (n = 2), Finland (n = 1), and nationally in Germany (n = 10), applying similar 8-hour curricula with 50% lectures and 50% hands-on training. The Given PillCam System was used in 12 courses, the Olympus EndoCapsule system in 5, respectively. A simple evaluation tool for capsule endoscopy training (ET-CET) was developed using 10 short SBCE videos including relevant lesions and normal or irrelevant findings. For each video, delegates were required to record a diagnosis (achievable total score from 0 to 10) and the clinical relevance (achievable total score 0 to 10). ET-CET was performed at baseline before the course and repeated, with videos in altered order, after the course. Two hundred ninety-four delegates (79.3% physicians, 16.3% nurses, 4.4% others) were included for baseline analysis, 268 completed the final evaluation. Forty percent had no previous experience in SBCE, 33% had performed 10 or less procedures. Median scores for correct diagnosis improved from 4.0 (IQR 3) to 7.0 (IQR 3) during the courses ( P < 0.001, Wilcoxon), and for correct classification of relevance of the lesions from 5.0 (IQR 3) to 7.0 (IQR 3) ( P < 0.001), respectively. Improvement was not dependent on experience, profession, SBCE system, or course setting. Previous experience in SBCE was associated with higher baseline scores for correct diagnosis ( P < 0.001; Kruskal–Wallis). Additionally, independent nonparametric partial correlation with experience in gastroscopy (rho 0.33) and colonoscopy (rho 0.27) was observed ( P < 0.001). A simple ET-CET demonstrated significant improvement of diagnostic skills on completion of formal basic SBCE courses with hands-on training, regardless of preexisting experience, profession, and course setting. Baseline scores for correct diagnoses show a plateau after interpretation of 25 SBCE before courses, supporting this number as a compromise for credentialing. Experience in flexible endoscopy may be useful before attending an SBCE course.